Interspecies interaction controls Escherichia coli growth in human gut microbiome samples - Mathilde Boumasmoud; Ricardo León-Sampedro; Vera Beusch; Fabienne Benz; Markus Arnoldini; Alex R. Hall (Proceedings of the National Academy of Sciences, 2026)
Gut microbial community composition varies from one person to another. Potentially, this means the ecological interactions experienced by individual strains or species also vary among microbiomes of different people. However, testing this directly in human microbiomes and identifying ecological drivers involved are challenging. Here, we use replicated anaerobic microcosms to quantify variability of population growth for a key commensal species among microbiome samples from different individuals and to identify underlying intra- and interspecific interactions. In a reciprocal transplant experiment, both absolute and relative growth performance of different Escherichia coli strains varied among gut microbiome samples from healthy individuals. This was partly explained by intraspecific competition: growth performance of individual E. coli strains was associated with displacement of resident conspecifics. However, the determinants of E. coli growth varied among samples. In one microbiome sample with a distinctive taxonomic composition, culture acidification by resident microbes impaired growth of all E. coli strains. We identified a strain of Clostridium butyricum contributing to this effect and showed that transferring it into other microbiomes predictably altered pH, fermentation product profiles (butyrate accumulation and acetate/lactate depletion), and population growth of other species including E. coli , thereby reshaping overall taxonomic composition. Our results suggest natural interindividual gut microbiome variation translates to variable ecological interactions with incoming bacteria, but these dynamics can be manipulated by a generalizable interspecies interaction.